2014
DOI: 10.1186/1476-511x-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOA5 rs662799 and rs3135506 polymorphisms with arterial hypertension in Moroccan patients

Abstract: BackgroundThe goal of the study is to investigate the association between the APOA5 polymorphisms and haplotypes with Arterial Hypertension (AHT) in Moroccan patients.MethodsThe study was performed in 283 subjects, 149 patients with AHT and 134 controls. All subjects were genotyped for the APOA5 -1131 T > C (rs662799), 56C > G (rs3135506) and c.553G > T (rs2075291) polymorphisms.ResultsThere was a strong association between -1131 T > C and 56C > G polymorphisms with AHT. The -1131 T > C and 56C > G polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…In our study TC and CC genotype of APOA5-1131T/C were more common in AMI patients with previous diagnosed hypertension than in patients without hypertension and had significant association with AMI patients. This result disagrees with the observation reported by Ouatou et al where data demonstrated that 56C>G SNP has a significant influence on blood pressure and triglyceride level (Ouatou et al, 2014). Although the association between diabetes and cardiovascular disease is unquestioned, the underlying mechanisms of the macrovascular complications are not well defined (Lardizabal et al, 2010).…”
Section: Discussioncontrasting
confidence: 61%
“…In our study TC and CC genotype of APOA5-1131T/C were more common in AMI patients with previous diagnosed hypertension than in patients without hypertension and had significant association with AMI patients. This result disagrees with the observation reported by Ouatou et al where data demonstrated that 56C>G SNP has a significant influence on blood pressure and triglyceride level (Ouatou et al, 2014). Although the association between diabetes and cardiovascular disease is unquestioned, the underlying mechanisms of the macrovascular complications are not well defined (Lardizabal et al, 2010).…”
Section: Discussioncontrasting
confidence: 61%
“…( Supplementary Table S12), involved in regulation of intestinal cholesterol absorption. Variants in some of these genes have been associated to high levels of LDL and total cholesterol (Bandarian et al 2013;the ENGAGE Consortium et al 2009) (Bandarian et al, 2013;the ENGAGE Consortium et al, 2009) (Bandarian et al 2013;the ENGAGE Consortium et al 2009) (Bandarian et al 2013;the ENGAGE Consortium et al 2009) as well as high triglyceride levels (Pennacchio et al 2002;Zhu et al 2014;Ouatou et al 2014), both factors leading to cardiovascular disease. The derived allele of rs3135506 in APOA-5 has the highest frequency in HUI compared to the other populations from the study and the TGP1000 ( Supplementary Table S12).…”
Section: Targets Of Adaptive Evolution In Nmmentioning
confidence: 99%
“…The derived allele of rs3135506 in APOA-5 has the highest frequency in HUI compared to the other populations from the study and the TGP1000 ( Supplementary Table S12). This missense mutation (S19W) has been associated with increased triglyceride levels and elevated risk of developing coronary artery disease in several populations including one labeled as "Hispanic" (Pennacchio et al 2002;Zhu et al 2014;Ouatou et al 2014). Moreover, HUI has the highest frequency of the missense mutation rs6756629 in ABCG5, which has been associated to increased total cholesterol and LDL (the ENGAGE Consortium et al 2009), a risk factor for coronary heart disease.…”
Section: Targets Of Adaptive Evolution In Nmmentioning
confidence: 99%
“…Literature report that about 50% of their final levels are genetically determined (Hubáček et al, 2009). Numerous studies have reported a significant association between the T1131C APOA5 variant and cardiovascular diseases development, especially myocardial infarction (MI) (Hubáček et al, 2003(Hubáček et al, , 2009Hubacek et al, 2004;Szalai et al, 2004;Zhou et al, 2013;Ouatou et al, 2014). However, this association was not observed in many other studies (Prochaska et al, 2010;Martinelli et al, 2007;Lee et al, 2004).…”
Section: Apoa5mentioning
confidence: 99%